Optical properties of functionalized Ti3C2T2 (T = F, O, OH) MXene: First-principles calculations - G. R. Berdiyorov (4435975) (2016)
Role of surface termination on the dielectric and optical properties of Ti3C2T2 (T = F, O, OH) MXene is studied using first-principles density functional theory. The results show that the surface functionalization has a significant impact on the optical properties of the MXene. For example, in the visible range of the spectrum, the oxidized sample shows larger absorption, whereas surface fluorination results in weaker absorption as compared to pristine MXene. In the ultraviolet energy range, all functional groups lead to the enhancement of both absorption and reflectivity of the material. Dielectric properties of MXene are also sensitive to the surface functionalization. Our findings demonstrate the importance of surface termination on the optical properties of the MXene. Other Information Published in: AIP Advances License: https://creativecommons.org/licenses/by/4.0/   See article on publisher's website: https://dx.doi.org/10.1063/1.4948799